LOS MILLENNIALS UNIVERSITARIOS Y SU INTERACCIÓN CON EL SOCIAL MOBILE - Dra. Sonia RUIZ BLANCO,Dr. Francisco Javier RUIZ SAN MIGUEL,Dr. Fermín GALINDO ARRANZ (Fonseca, Journal of Communication, 2023)
In the past few years College professors has the challenge of teaching the so-called “Generation Y” or “Millennials”, ie the age group born between 1980 and 2000 who raise with the existence of the Internet, which implies an approach to knowledge and learning different from previous generations. At college, especially more experienced professors are concerned over the possibility that learners knows these tools better than the professor himself, however,professors who have learned to use these new technologies have observed, surprisingly, as this age group can get to know many tools but not their proper use, in personal or professional environment.